1995
DOI: 10.1021/j100025a029
|View full text |Cite
|
Sign up to set email alerts
|

Equation of State of Hydrogen-Bonded Polymer Solutions: Poly(4-hydroxystyrene) + Ethanol and + Tetrahydrofuran

Abstract: We have measured the equation of state surface for the mixtures poly(4-hydroxystyrene) + ethanol, and + tetrahydrofuran below 40 MPa. The results obey a superposition principle that makes it possible to build a master curve once the p-V-T surface is known at a given pressure. The master curve depends on a single system-dependent parameter that, for the two systems studied, takes almost the same value. The results have been analyzed with a lattice fluid model that includes the existence of hydrogen bonds. Even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…The purpose of the present work is to carry out a precise study of the p − V − T surface mixtures formed by PPG + n -hexane and PPG + ethanol, over the whole composition range. The data is correlated in terms of the EoS developed by Panayiotou and Sanchez 25 and compared with those previously reported for P4HS + ethanol . A similar study for aqueous systems of PPG, PPG + PEG, and the copolymer will be reported in a future work.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The purpose of the present work is to carry out a precise study of the p − V − T surface mixtures formed by PPG + n -hexane and PPG + ethanol, over the whole composition range. The data is correlated in terms of the EoS developed by Panayiotou and Sanchez 25 and compared with those previously reported for P4HS + ethanol . A similar study for aqueous systems of PPG, PPG + PEG, and the copolymer will be reported in a future work.…”
Section: Introductionmentioning
confidence: 65%
“…The p − ρ− T data have been measured using a modified Anton-Paar Model DMA 512 high-pressure vibrating tube densitometer, as in a previous work . The densitometer was calibrated with eight pure substances according to the procedure described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental set-up has been described in previous work. 25 The densitometer was calibrated with eight pure substances according to the procedure described elsewhere. 26 To account for the inÑuence of the viscosity of the sample, we have followed the method of Ashcroft et al using glycerol as the reference.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the tabulated PVT data by Danner and High [1], Zoller and Walsh [2] for a variety of polymeric materials and some of polymer solutions and polymer blends, Sandell and Goring [3] and Muller and Rasmussen [4] measured the densities of aqueous oligomeric propylene glycols and aqueous PEG mixtures, respectively. To study the specific interactions between polymers and solvents, Compostizo and coworkers [5][6][7][8] have measured the volumetric properties for various polymer solutions and blends: {poly(4-hydr oxystyrene) + acetone}, {poly(4-hydroxystyrene) + tetrahydrofuran}, {poly(4-hydroxystyrene) + ethanol}, {poly(propylene glycol) (PPG) + n-hexane}, (PPG + ethanol), and (PEG + PPG). Other sources of PVT values for polymeric mixtures are (poly(phenyl oxide) + polystyrene} [9], {polystyrene + poly(vinyl methyl ether)} [10], {poly(vinyl fluoride) + hexafluoropropylene} [11], and {poly-styrene + tetramethyl bisphenol-A polycarbonate} [12].…”
Section: Introductionmentioning
confidence: 99%